Application Research of an Automatic Control Seawater Reverse Osmosis (SWRO) System Based on the Siemens PLC - Li, Qihang; Li, Kai; Yuan, Canming (Global Journal of Earth Science and Engineering, 2024)
To solve the global environmental problem of a shortage of freshwater resources, seawater desalination is considered one of the most promising solutions. In this research, the main novelty of the seawater desalination system lies in its utilization of a reverse osmosis unit as the core process for producing drinking water. By optimizing the pretreatment section in the process flow, a seawater reverse osmosis (SWRO) control system based on Siemens PLC with a high degree of automation was developed, which has the advantages of convenient maintenance and monitoring. In addition, through research on reverse osmosis systems, the results showed that within two years of operation, the total desalination rates of the primary and secondary reverse osmosis systems were not less than 99% and 97.5%, respectively. Furthermore, the water quality after desalination was tested. When the doses of CaCl2, MgCl2 and NaHCO3 were 20 mg/L, 15 mg/L, and 50 mg/L, respectively, high-quality drinking water was obtained. Finally, a reasonable process plan and corresponding estimates were given for the complex water source conditions. Compared with traditional seawater desalination systems, our system has the advantages of easy operation, efficient water production and lower price. Accordingly, this study will help to solve drinking-water problems in some freshwater-scarce regions.